Citizen Participation and the Performance of Subnational Governments: a Literature Review - Hernández Bonivento, José; Miranda Orrego, Juan Pablo (Revista del CLAD Reforma y Democracia, 2019)
There is a long-standing debate in the literature about the effects that citizen participation can have on the efficacy and efficiency of government, particularly at subnational level. Much of the discussion has focused on the potential that citizen participation holds for local democracy. However, doubts remain about whether participative mechanisms and citizenship involvement can contribute to improving these actions of the local state. This paper therefore carries out a systematic review and meta-analysis of the literature, in order to discover what light specialist research can throw on this debate. After the analysis described, the results show that most studies reveal a positive relationship between citizen participation and the improvement of government performance, based on both theoretical and empirical analysis, highlighting the potential in terms of improving the provision of public services, in the consolidation of democratic values and in the construction of trust between citizens and public administration. However, there are also evidence of blocking factors that could generate negative and counterproductive effects. It concludes with an analysis of the results and a brief agenda for future research.
Keywords: Citizen Participation; Performance Improvement; Performance; Efficiency; Efficacy; Effectiveness; Governance; Local Government